2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33465
|View full text |Cite
|
Sign up to set email alerts
|

Trash Teachings: How a Materials Science Module Series about Waste can Empower Engineering Students to be More Sociotechnically Responsible

Abstract: is a post-doctoral research associate in the General Engineering department in the Shiley-Marcos School of Engineering, where she innovatively integrates social justice, humanitarian advancement, and peace into the traditional engineering curriculum. Before joining USD in August 2017, Bre spent 9 years at Clemson University, where she was a three-time graduate of the bioengineering program (BS, MS, and PhD), founder of The Design & Entrepreneurship Network (DEN), and Division I rower. In her spare time, Bre te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This place-based and culturally sustaining pedagogical model advances the literature on how to develop sociotechnical, sustainability-focused engineering curricula [3][4][5][6][7][8][9][10][11][12][13][14][15] and complements the model proposed by Gelles and Lord for integrating sociotechnical modules into materials science classes [8]. We were particularly pleased to see that the students exhibited critical thinking using data from the course content and student presentations, considering multiple approaches for water treatment, and comparing and contrasting these models.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This place-based and culturally sustaining pedagogical model advances the literature on how to develop sociotechnical, sustainability-focused engineering curricula [3][4][5][6][7][8][9][10][11][12][13][14][15] and complements the model proposed by Gelles and Lord for integrating sociotechnical modules into materials science classes [8]. We were particularly pleased to see that the students exhibited critical thinking using data from the course content and student presentations, considering multiple approaches for water treatment, and comparing and contrasting these models.…”
Section: Discussionmentioning
confidence: 93%
“…We situated the course in the sociotechnical engineering paradigm, in which engineers wholistically explore and consider the 'socio' elements of an engineering topic or project (cultural, economic, environmental, political, etc.) interlinked with the technical [3][4][5][6][7][8][9][10][11][12][13][14][15]. The course was taught previously by another instructor; however, we redesigned it using place-based and culturally sustaining pedagogies (CSPs), which emphasize a connection between the students' lived experiences and their course experiences [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Not only has our research shown that sociotechnical contexts can enhance students' learning of technical content [27]- [33], but sociotechnical thinking is critical for tackling the complex problems we face today globally [34]. After all, engineering alone cannot solve complex sociotechnical issues [35].…”
Section: Project Contextmentioning
confidence: 99%
“…We have published an overview of some of these efforts [1,2]. We have also published details about modules in existing courses including Statics [3,4], Heat Transfer [5] and Robotics [6] in Mechanical Engineering, Circuits [7,8] in Electrical Engineering, Operations Research [9] in Industrial & Systems Engineering, and Introduction to Materials Science [10,11,12]. In addition, we have described courses on User-Centered Design (UCD), Engineering and Social Justice [13], and an elective on Engineering Peace [14,15,16,17].…”
Section: Summary Of Curriculum Developmentmentioning
confidence: 99%